Educação permanente em saúde: práticas humanizadas no centro obstétrico de um hospital universitário - Silva, Ursula Gliesch (Universidade do Vale do Rio dos Sinos, 2013)
This study aimed to propose alternatives in order to improve humanized care practices in the Obstetric Center of an University Hospital, through the Permanent Health Education.The main and in order to achieve this, it was necessary to first identify which humanized practices care currently occur in the O C and to find out difficult points and facilitating points to disseminate humanized care practices. This study path was an exploratory-descriptive research with a qualitative approach, where afocus group technique fordatacollect was used. The data analysis allowed to emergefour categories: a)team perception about humanized practices, 2)depersonalized work and robotic care,3) the care fragmentation and the power relation, 4)and the disposal for health professionals to learn. The research shows us ways to develop educational programs that enable to health workers to rethink the current model, working collectively difficulties, recover every individual characteristics involved in care taking through dialogue and subjective relations investment arising from the encounter with the other and these strengthen the focus of humanized practices.
Keywords: Educação permanente em saúde; Humanização do cuidado; Parto humanizado; Enfermagem; Hospital universitário; Health education; Humanization of assistance; Humanizing delivery; Nursing; Hospitals; University; ACCNPQ::Ciências da Saúde::Enfermagem